Knowlesi Malaria - Lau , Yee Ling (University of Malaya, 2020)
Originally a simian malaria, Plasmodium knowlesi is now known as the fifth human malaria species. Since the report of a large focus of human knowlesi cases in Sarawak in 2004, many more human cases have been reported in all of the countries in Southeast Asia and in travellers returning from these countries. The zoonotic nature of this infection hinders malaria elimination efforts. In order to grasp the current perspective of knowlesi malaria, this inaugural lecture explores the different aspects of the disease including risk factors, diagnosis, treatment, molecular and functional studies. Current studies do not provide sufficient data for an effective control programme. Therefore, future direction for knowlesi research is highlighted here with the final aim of controlling, if not eliminating the parasite.